2020
DOI: 10.1186/s12885-020-07630-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor-mutant non-small cell lung Cancer and Choroidal metastases: long-term outcome and response to epidermal growth factor receptor tyrosine kinase inhibitors

Abstract: Background Choroidal metastases are the most common eye metastatic site. The prevalence of choroidal metastases in NSCLC patients has been reported to vary from 0.2 to 7% in historical series. Although previously reported, little is known about choroidal metastasis in Epidermal Growth Factor Receptor (EGFR)-mutant Non-small cell lung cancer (NSCLC). This study sought to describe the prevalence of choroidal metastases among patients with EGFR-mutated NSCLC and their characteristics, and to estimate their impact… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
(31 reference statements)
0
14
0
Order By: Relevance
“…[ 5 ] Additionally, the presence of choroidal metastasis may occur in up to 8.4% of primary cases of EGFR + NSCLC. [ 6 ] The mean age of diagnosing uveal metastasis is 60 years and blurry or disturbed visual acuity is the most common presenting symptom. [ 1 , 7 , 8 ] In addition to blurry vision, the patient did report mild fatigue and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 ] Additionally, the presence of choroidal metastasis may occur in up to 8.4% of primary cases of EGFR + NSCLC. [ 6 ] The mean age of diagnosing uveal metastasis is 60 years and blurry or disturbed visual acuity is the most common presenting symptom. [ 1 , 7 , 8 ] In addition to blurry vision, the patient did report mild fatigue and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“… 6 It has been reported that the prevalence of choroidal metastases ranges from 0.2 to 7% in cases with NSCLC 7 , 8 with a recent case series showing the prevalence to be 8.4% in NSCLC cases with an EGFR mutation. 9 …”
Section: Introductionmentioning
confidence: 99%
“…Tyrosine kinase inhibitors (TKIs) targeting the EGFR pathway have become the gold standard of treatment for EGFR-mutated NSCLC. First and second generation EGFR-TKIs, such as gefitinib, erlotinib, or afatinib, have shown efficacy in treating choroidal metastasis, 9 , 10 , 11 but an EGFR T790 M resistance mutation can occur that limits the systemic efficacy of these treatments. 12 Osimertinib is an oral, third-generation, irreversible EGFR-TKI that selectively inhibits both EGFR-TKI–sensitizing and EGFR T790 M resistance mutations and has been shown to have improved overall survival over first generation EGFR-TKIs in previously untreated advanced stage NSCLC patients, as well as improved efficacy in the CNS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tyrosine kinase receptors of the ERBB family include four members: HER-1/ERBB1/EGFR, HER-2/ERBB2, HER-3/ERBB3, and HER-4/ERBB4 (Bouchez et al 2020 ; Li et al 2016 ). The previous research has indicated that the ERBB receptor family is closely associated with cell proliferation and oncogenic events (Hyman et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%